2004
DOI: 10.1101/gad.306504
|View full text |Cite
|
Sign up to set email alerts
|

The activity of the Nodal antagonist Cerl-2 in the mouse node is required for correct L/R body axis

Abstract: Correct establishment of the left/right (L/R) body asymmetry in the mouse embryo requires asymmetric activation of the evolutionarily conserved Nodal signaling cascade in the left lateral plate mesoderm (L-LPM). Furthermore, the presence of Nodal in the node is essential for its own expression in the L-LPM. Here, we have characterized the function of cerl-2, a novel Nodal antagonist, which displays a unique asymmetric expression on the right side of the mouse node. cerl-2 knockout mice display multiple lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
214
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(221 citation statements)
references
References 36 publications
7
214
0
Order By: Relevance
“…Thus, this domain is regarded to be the organizing center of the left-right axis in the zebrafish embryo. Recently, mouse Cerberuslike 2 (Cerl-2; Dante) was identified and this molecule also plays a key role in restricting the Nodal signaling toward the left side by preventing its activity in the right side (Marques et al, 2004). In Xenopus embryos, expression of the gene coding for a member of Cerberus/Dan family such as Charon or Cerl-2 at the tail region has not yet been reported.…”
Section: Relationships Between Posterior Bilateral Xnr-1 Expression Amentioning
confidence: 99%
“…Thus, this domain is regarded to be the organizing center of the left-right axis in the zebrafish embryo. Recently, mouse Cerberuslike 2 (Cerl-2; Dante) was identified and this molecule also plays a key role in restricting the Nodal signaling toward the left side by preventing its activity in the right side (Marques et al, 2004). In Xenopus embryos, expression of the gene coding for a member of Cerberus/Dan family such as Charon or Cerl-2 at the tail region has not yet been reported.…”
Section: Relationships Between Posterior Bilateral Xnr-1 Expression Amentioning
confidence: 99%
“…Rather, Cerberus-related proteins are key regulators of Nodal signaling and play an important role in the establishment of left -right asymmetry in the vertebrate embryo (Rodriguez Esteban et al 1999;Yokouchi et al 1999;Zhu et al 1999;Hashimoto et al 2004;Marques et al 2004;Tavares et al 2007;Vonica and Brivanlou 2007).…”
Section: Cerberusmentioning
confidence: 99%
“…These results thus suggested that the amount of Nodal-GDF1 produced in the node is reduced in the high-glucose condition. Expression of Nodal in the left LPM requires the activity of Nodal in crown cells to be regulated in an L-R asymmetric manner, with Cerl2 playing an essential role in such regulation through suppression of Nodal activity (32,33,35). Cerl2 is expressed in crown cells, with the level of expression being higher on the right side.…”
Section: Resultsmentioning
confidence: 99%
“…Nodal produced in the crown cells of the node is required for the subsequent expression of Nodal in the left LPM (30,32,37). We therefore next examined whether the expression of Nodal-related genes, including Nodal, Gdf1, and Cerl2, was affected in the node of highglucose embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation